Prevalence of Prostate Cancer Risk Factors and Symptoms in Indigenous People in Tabasco, Mexico - Sánchez Sánchez, Kristell; Cruz Sánchez , Marcelina; Rivas Acuña , Valentina; Pérez Chan, Manuel (Revista Cuidarte, 2021)
Introduction: Prostate cancer is a public health problem being the most frequently diagnosed neoplasm and the second leading cause of cancer death in men. However, there is little information about this disease in indigenous people and therefore, current knowledge calls for urgent primary prevention. Objective: To analyze the prevalence of prostate cancer risk factors and symptoms in indigenous men in Centro, Tabasco. Materials and Methods: A cross-sectional descriptive correlational study was conducted with 281 Chontal men aged 40 years and older from the communities of Tamulté de las Sabanas, Aniceto and Tocoalt. The Prostate Symptom Score questionnaire and interviews for assessing risk factors were both implemented. Results: 52.7% had no formal schooling at all, 47.7% were peasants at an average age of 55 years, 16.7% had moderate to severe prostatic symptoms. As for risk factors, 44.5% were classified to be at medium risk and 55.5% at high risk. Pearson’s chi-squared test between variables age and prostatic symptoms showed an association of p=.000 and a value of p=.166 between age and risk factors. Younger men showed to have more risk factors associated. None had undergone comprehensive screening. Discussion and Conclusions: Prevalence of prostatic symptoms found in older adults is consistent with other studies. Prevalence of risk factors in all participants is a matter of concern as these are the same risk factors observed in men diagnosed with prostate cancer. It is important to develop prevention strategies based on healthy lifestyles.How to cite this article: Sánchez-Sánchez Kristell, Cruz-Sánchez Marcelina, Rivas-Acuña Valentina (+), Pérez-Chan Manuel. Prevalencia de factores de riesgo y sintomatología prostática en indígenas de Tabasco. Prevalencia de factores de riesgo y sintomatología prostática en indígenas de Tabasco. Revista Cuidarte. 2021;12(2):e1264. http://dx.doi.org/10.15649/cuidarte.1264
Keywords: Prostatic Neoplasms; Risk Factors; Indigenous Population